Peri‐implant tissue conditions at implants treated with Sub‐periosteal Peri‐implant Augmented Layer technique: A retrospective case series. Issue 10 (1st September 2020) - Trombelli, Leonardo; Pramstraller, Mattia; Severi, Mattia; Simonelli, Anna; Farina, Roberto
Abstract: Objectives: To assess peri‐implant tissue conditions on the short term in patients receiving the Sub‐periosteal Peri‐implant Augmented Layer (SPAL) technique and in patients with adequate thickness (≥2 mm) of the peri‐implant buccal bone plate (PBBP) at placement. Methods: Patients where either a dehiscence defect or thin PBBP at implant placement was corrected by SPAL technique (SPALdehiscence and SPALthin groups, respectively) and patients presenting a residual PBBP thickness ≥2 mm at implant placement (control group) were retrospectively selected. The number of peri‐implant sites positive to bleeding on probing (BoP) at 6 months following prosthetic loading was the primary outcome. Also, height of keratinized mucosa, marginal soft tissue level, Plaque Index, peri‐implant probing depth, suppuration on probing, and interproximal radiographic bone level (RBL) were evaluated. Results: Thirty‐four patients (11 in the SPALdehiscence group, 11 in the SPALthin group, and 12 in the control group) were included. In each SPAL group, 10 patients (90.9%) showed peri‐implant tissue thickness ≥2 mm at the most coronal portion of the implant at uncovering. The prevalence (number) of BoP‐positive sites was 2, 1, and 0 in the SPALdehiscence, SPALthin, and control groups, respectively. RBL amounted to 0.3 mm in the SPALdehiscence group, 0.2 mm in the SPALthin group, and 0 mm in the control group. Conclusion: After 6 months of prosthetic loading, patients treated with SPAL technique show limited peri‐implant mucosal inflammation in association with shallow PD and adequate KM. At implants receiving SPAL technique, however, interproximal RBL was found apical to its ideal position.